Novel dual binding site inhibitors of acetylcholinesterase designed with a carbazole ring using molecular modeling - هلال, محمود; فاتن الشب (Latakia University Journal -Medical Sciences Series, 2023)
Acetylcholinesterase (AChE) inhibitors play an important role in Alzheimer's disease (AD). These inhibitors are the FDA-approved first-line AD therapy as they increase the levels of acetylcholine (ACh). In addition, they can also interfere with AD pathophysiology by preventing the accumulation of β-amyloid (Aβ) plaques. This study aimed to find effective and dual binding site inhibitors of AChE using molecular modeling. In this work, a library of chemical compounds derived from carbazole was designed to meet the structural requirements of AChE inhibitors. Molecular docking studies were performed for the compounds, and interaction modes with enzyme active sites were determined. Docking studies indicated a strong interaction between the active site of AChE and C16, C22 from the carbazole core.The pharmacokinetics properties and blood-brain barrier permeability of the compounds were investigated.